Analisis Pelaksanaan Penerbitan Surat Tanda Registrasi pada Tenaga Kesehatan di Provinsi Sumatera Selatan - Yuliani, Deasi; Lisdiana, Lisdiana; Mahriadi, Nopriawan (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2026)
The research entitled Implementation of Issuance of Registration Certificates to Health Workers in South Sumatra Province, identified the problem of lack of knowledge of health workers about the procedures for handling registration certificates and the lack of role of the South Sumatra Provincial Health Office in supervising and fostering procedures for managing registration certificates Analysis design using descriptive analysis methods which are carried out through several stages, namely condensing data, data presentation, conclusion drawing and verification with the South Sumatra Provincial Health Office. Data were collected through literature studies, observations and interviews. The technique of checking data abstraction is carried out through the extension of participation time, observation, triangulation and peer checking as well as the emergence of references. This research uses Terry's theory (2006), namely by looking at four factors, namely: Planning, Organizing, Implementation and Supervision. Based on the results of the study, it was revealed that even in terms of service, officers are always quick to answer if there are applicants who are still confused about the procedures for managing new moving services, the responsibility of the South Sumatra Provincial Health Office in carrying out the issuance of STRs has been implemented properly, it's just that there is still a lack of number of STRs printed due to the lack of role of the South Sumatra Provincial Health Office in supervising and fostering handling procedures certificates while in the implementation of the STR Issuance has been carried out, all files are uploaded through the https://ktki.kemkes.go.id/registrasi website or come directly to the South Sumatra Provincial Health Office because they will be assisted starting from the registration process, data collection and examination, verification of data filing, although the response of officers to reply to incoming messages from the public is slow. The South Sumatra Provincial Health Office has been doing well; whereas in the case of monitoring there is no coordination related to the development of online regitration socialization in the implementation of STR issuance, there are Applicants who do not understand the procedure.